Darsi codici etici in antropologia: Riflessioni a margine del processo di adozione del codice deontologico della Società Italiana di Antropologia Applicata - Bassi, Marco (Antropologia Pubblica, 2024)
Through review of selected anthropological ethical codes an attempt is made to outline the fundamental ethical principles of anthropological research and their applicability to current practices of applied anthropology. The Statement on Problems of Anthropological Research and Ethics was adopted by the American Anthropological Association in response to the need to take distance from military research after the Camelot scandal. Anthropology reacted stronger than other disciplines due to its methodology implying a relation of trust with the community. The Codice etico of AISEA defines the anthropologist’s obligations with different type of actors. In applied anthropology more attention should be paid to the relation with the financers of the research, due to possible conflict of interest between the latter and the concerned community. During consultancies anthropologists are today often forced into conditions that do not allow them to fulfil the obligations as stated in most deontological codes. Yet, giving up would cut the anthropologist out of the ongoing processes that have often a potential critical impact on the communities. The Codes of Ethics of ISE has allowed overcoming serious controversies by referring to procedural rights according to international law. It is suggested that reference to procedural and collective rights, appropriate international standards and best practices can provide an appropriate device to evaluate case by case the opportunity to engage, considering the overall field of relations rather that strictly focusing on the anthologist’s obligations which each actor independently.